Noninvasive vagus nerve stimulation for migraine: a systematic review and meta-analysis of randomized controlled trials - Song, Dong; Li, Piaoyi; Wang, Yonggang; Cao, Jin (Frontiers in Neurology, 2023)
Background: Medication is commonly used to treat migraine. However, patients may experience adverse events, or a lack of efficacy from medicine. In recent years, neuromodulation techniques have emerged as potential non-pharmacological therapy for migraine. This article focuses on a systematic review and meta-analysis of randomized controlled trials of non-invasive vagus nerve stimulation (n-VNS) for migraine to determine the efficacy, safety and tolerability of n-VNS. Methods: We searched PUBMED, EMBASE, and Cochrane Center Register of Controlled Trials databases up to July 15, 2022. Primary outcomes were migraine or headache days, and pain-free rates within 2 hours. Secondary outcomes were ≥50% responder rate, headache intensity, monthly acute medication reduction days, and adverse events. Results: Meta-analysis shows that non-invasive cervical vagus nerve stimulation (n-cVNS) significantly impacted ≥50% responder rate (OR, 1.64; 95% CI, 1.1 to 2.47; p=0.02), but had no significant effect on reducing migraine days (MD, -0.46; 95% CI, -1.21 to 0.29; p=0.23), headache days (MD, -0.68; 95% CI, -1.52 to 0.16; p=0.11). In contrast, low-frequency non-invasive auricular vagus nerve stimulation (n-aVNS) was found to significantly reduce the number of migraine days (MD, -1.8; 95% CI, -3.34 to -0.26; p=0.02), and headache intensity (SMD, -0.7; 95% CI, -1.23 to -0.17; p=0.009), but not the number of acute medication days per month (MD, -1.1; 95% CI, -3.84 to 1.64; p=0.43). In addition, n-VNS devices were found safe and well-tolerated in most patients. Conclusion: These findings show that n-VNS is a promising method for migraine management.